Grandchildren and Their Grandparents' Labor Supply - Peter Rupert; Giulio Zanella (Institute of Labor Economics (IZA), 2017)
Working-age grandparents supply large amounts of child care, an observation that raises the question of how having grandchildren affects grandparents' own labor supply. Exploiting the unique genealogical design of the PSID and the random variation in the timing when the parents of first-born boys and girls become grandparents, we estimate a structural labor supply model and find a negative effect on employed grandmother's hours of work of about 30% that is concentrated near the bottom of the hours distribution, i.e., among women less attached to the labor market. Implications for the evaluation of child care and parental leave policies are discussed.
Keywords: D19; J13; J14; J22; 330; labor supply; grandparents; child care